القواعد الفقهية المبنية على أصل الاستصحاب وأثرها فى المعاملات المالية - Azli Fairuz bin Laki (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2011)
This research is aimed at investigating Islamic legal maxims based on Al-Istishab principle and its implication on modern financial transactions. It examines the definition of legal maxim, its sources, validity and importance from the Islamic jurisprudence perspective and also sheds light on the conception, types and validity of Al-Istishab from the Usuli point of view. Then, the research focuses on a number of relevant legal maxims which are directly related to financial transactions, represented by one of the five universal Islamic legal maxims which means: “Certainty shall not be removed by Doubt” and other related legal maxims which have been derived on its basis, by clarifying the meaning and evidence from the Qur'anic text and Prophetic Sunnah. The study has also compiled some of the Islamic jurisprudential practices regarding financial transactions for these maxims, mostly as discussed in classical literature. The research has adopted two methodologies; the inductive method which is based on collecting the relevant legal text as mentioned by classical and modern Muslim scholars, and the analytical method to discuss and analyze these scholars' views and to recommend the most appropriate ones. To portray the relevance and effectiveness of these legal maxims in contemporary transactions, the application of Islamic legal maxims based on Al-Istishab is exemplified in a number of modern financial contracts and terms of contracts, namely Contract of Insurance, Contract of Construction, issues of penalty clause for non-fulfillment of contract, conditional maintenance which is included in the sales contract which requires the maintenance worker to provide service and conditional maintenance in the rent contract which is the responsibility of the renter. Eventually, this study establishes the importance of reliance on these Islamic legal maxims in terms of making the Islamic Jurisprudence able to cope and absorb the development of financial transactions despite the renewal and complexity as they represent a manifestation of adaptability, vitality, flexibility and validity that eases human dealings and transactions.